From labour market to educational system: the case of ESCO - Winch, Christopher [Verfasser] (My University, 2025)
„The article describes the European labour market tool ESCO and its relationship to other European vocational tools. It is shown how ESCO can be used to structure occupations by aggregating skills and construct qualifications by mapping skills onto learning outcomes. However, qualifications constructed in this way are inadequate for a skilled labour market and often do not represent national traditions of occupational competence. The article concludes by suggesting an alternative approach to securing occupational mobility through qualifications.“ (author‘s abstract; BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; 370; ESCO; Anerkennung; Auslandsqualifikation; Europa; Arbeitsmarkt; Berufsprofil; Kompetenzfeststellung; Lernergebnisorientierung